Pengaruh Harga, Citra Merek, Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Pengguna Produk Rabbani - Fina Rahma Naisaniya; Edy Purwo Saputro (VALUE, 2023)
The purpose of this study is to examine the impact of price, brand image, and product quality on purchasing decisions among users of Rabbani products. This research falls into the category of descriptive research with a research method that uses a quantitative approach. The population of this study includes all students at Universitas Muhammadiyah Surakarta who have purchased Rabbani products. To determine the sample size, this study refers to Malhorta's theory, which says that the sample size can be calculated by multiplying the number of question items by at least four or five. Therefore, the number of samples in this study was 100 respondents. The sampling technique used in this study was non-probability sampling with purposive sampling method. This research was conducted using Partial Least Square (PLS) with the help of Smart PLS software version 3. The results of the analysis in this study indicate that price has a positive but insignificant impact on purchasing decisions, brand image has a negative and insignificant impact on purchasing decisions, while product quality has a positive and significant impact on purchasing decisions.